ZOOM MEETING: SOLUSI DALAM DIKLAT ONLINE CALON KEPALA LABORATORIUM/BENGKEL SEKOLAH/MADRASAH DI MASA PANDEMI COVID-19 - Manganju Manik (Jurnal Pendidikan, 2021)
During the Covid-19 pandemic, which is still ongoing in Indonesia, it is unlikely that you will be able to hold face-to-face learning activities in classrooms or meeting rooms.Many education and training activities have been delayed due to the Covid-19 pandemic. Whereas currently, there are many middle school or madrasah teachers who want to take part in education and training activities to increase competency for prospective laboratory heads.In the education and training of prospective heads of laboratories/workshops school/madrasah, the organizers have prepared an e-learning or online education and training system.In this online education and training, organizers use the zoom meeting application as a learning tool.From the background, the purpose of this study is to provide an overview / description and explanation of the use of zoom meetings in online education and training for prospective heads of laboratories/workshops school/madrasah using qualitative descriptive methods and filling out questionnaires. The conclusion of this research is that training participants can use the zoom meeting application during online education and training easily and the use of the zoom meeting application has several features that can support and be a great solution to help facilitate all learning processes, especially in online education and training for prospective heads of laboratories/workshops school/madrasah during the Covid-19 pandemic.